Volume Disorders as a Mechanism of Multiple Organ Dysfunction Syndrome and Associated Lethality - Popov , Alexander S. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present study was to evaluate the significance of volume status in critically ill patients for assessment of volume status influence of fluid-related sectoral disorders on the associated lethality.Methods. The authors studied 256 clinical cases of patients with multiple organ dysfunction syndrome aged from 18 to 78 (average age 62.4 ± 8.8) regardless of sex, hospitalized to units of resuscitation and intensive care.The dynamics of general clinical parameters (central hemodynamics, respiratory status, pulseoxymetry parameters, hemoconcentration parameters, plasma albumins) was studied. The severity of patients conditions was assessed by three-level scale of intensive care patients condition severity, consciousness impairment – by Glasgow scale, volume status – by the severity and localization of edemas, presence of free fluid in organism cavities and central venous pressure. Body fluids and volume of circulating blood were measured by bioimpedance method. Infusion plan (volume, quality and ratio of media, fluid balance) was assessed. Multiple Organ Failure Scale along with the developed Scale of Fluid-Related Sectoral Disorders Evaluation was used for assessment of patients status in critical conditions and organ failure associated lethality.Results. The authors identified 4 groups of patients by the severity of volume disorders: 49.6% of patients were in Group 2 (lethality in 20.8%); 27.4% were in Group 3 (lethality in 37.6%); 9.7% were in Group 4 (lethality in 72.5%); the rest patients were included into Group 1 (lethality in up to 10%). Direct correlation was identified between the severity of volume disorders and lethality. It was proved that volume disorders were one of the main consecutively determined mechanisms of multiple organ dysfunction syndrome development.Conclusion. The infusion therapy for multiple organ dysfunction syndrome was primarily aimed at normalization of fluid-related sectoral homeostasis (normovolemia). For systematization of the parameters of fluid-related sectoral disorders, further distribution of the patients by the influence of the mentioned disorders on the disease outcome and dynamic control of volume status, the authors developed formalized scale for evaluation of volume disorders and prognosis of lethality risk in patients with multiple organ dysfunction syndrome.